PENGGUNAAN ONGGOK SEBAGAI ADITIF TERHADAP KANDUNGAN NUTRIEN SILASE CAMPURAN DAUN UBIKAYU DAN GAMAL - Nonok Supartini (BUANA SAINS, 2011)
The experimental methods and design was carried out by Completely Randomized Design (CRD) with four treatments, replicated five times and 21 day long fermentation process. Based on analysis of variance showed that average DM (Dry Matter) content in each treatment amounted were: P0 = 22,83%; P1 = 23,58%; P2 = 25,12% and P3 = 26,95%. Average OM (Organic Matter) content were: P0 = 91,05%; P1 = 91,01%; P2 = 90,59% and P3 = 91,74%. Average CP (Crude Protein) content were: P0 = 20,91%; P1 = 21,08%; P2 = 22,33% and P3 = 22,81%. Based on analysis of variance showed that different level of onggok gave significant difference (P